TİMPANOSKLEROZLU KRONİK OTİTİS MEDİALI HASTALARDAKİ ANTİOKSİDAN ENZİMLERİN GENETİK POLİMORFİZMİ - AKYİĞİT, ABDULVAHAP (Fırat Üniveristesi, 2011)
Bu çalışmada timpanosklerozlu (TS) kronik otitis medialı (KOM) hastalarda indüklenebilir nitrik oksit sentetaz (iNOS), süperoksit dismutaz (SOD) ve katalaz enzimlerinin genetik polimorfizmi değerlendirilerek, TS etiyolojisinde genetik yatkınlığın rolü araştırılmıştır.Çalışmaya KOM nedeniyle opere edilen 64 hasta ve kulak problemi veya bilinen kronik sistemik bir hastalığı olmayan 32 birey alınmıştır. Timpanosklerozlu KOM, timpanosklerozsuz KOM ve kontrol grubu olmak üzere üç grup oluşturulmuştur. Hastalardan ve kontrol grubundan alınan venöz kan örneklerinden DNA izolasyonu yapılmış, revers transkriptaz polimeraz zincir reaksiyon (RT PZR) incelemesi ile de genetik polimorfizm değerlendirilmiştir.İndüklenebilir nitrik oksit sentetaz genindeki (-277) A/G polimorfizm için GG genotip dağılımı timpanosklerozlu KOM, timpanosklerozsuz KOM ve kontrol grubunda sırasıyla 13 (%40), 7 (%22) ve 4 (%12) olarak bulunmuştur. Timpanosklerozlu KOM grubu ile kontrol grubu arasında GG genotip dağılımı açısından istatistiksel olarak anlamlı fark bulunmuştur (p=.008).Süperoksit dismutaz (mn-SOD) A16V (C/T) polimorfizmi için CC genotip dağılımı timpanosklerozlu KOM, timpanosklerozsuz KOM ve kontrol grubunda sırasıyla 8 (%25), 7 (%22) ve 4 (%12) olarak bulunmuştur. Timpanosklerozlu KOM grubu ve timpanosklerozsuz KOM grubunda, kontrol grubuna göre CC genotip sayısında artış görülmesine rağmen istatistiksel olarak anlamlı farklılık bulunmamıştır (p>0.05).Katalaz geninde -21 pozisyonundaki A/T değişim polimorfizmi için TT genotip dağılımı timpanosklerozlu KOM, timpanosklerozsuz KOM ve kontrol grubunda sırasıyla 6 (%20), 2 (%6) ve 3 (%9) olarak bulunmuştur. Timpanosklerozlu KOM grubunda, kontrol grubuna göre TT genotip sayısında artış görülmesine rağmen istatistiksel olarak anlamlılık belirlenmemiştir (p>0.05).Bu çalışmada sağlıklı bireylere göre timpanosklerozlu KOM' lu hastalarda, iNOS geninde (-277) GG genotipinin anlamlı düzeyde artmış olduğu tespit edilmiş ve timpanosklerozun etyopatogenezinde genetik yatkınlığın rol oynayabileceği düşünülmüştür.Anahtar Kelimeler: Timpanoskleroz, İndüklenebilir Nitrik Oksit Sentetaz, Süperoksit Dismutaz, Katalaz, Genetik Polimorfizm

In this study, genetic polymorphism of inducible nitric oxide synthetase (iNOS), superoxide dysmutase (SOD) and catalase enzymes were analyzed in patients with thympanosclerosis (TS) chronical otitis media (COM), therefore role of genetic predisposition in TS etiology was researched.32 persons who did not have any ear problem or known chronical systemic disease, and 64 patients who were operated because of COM were included in this study. Three groups were created: COM with thympanosclerosis, COM without thympanosclerosis and the control group. DNA insulation was performed from venous blood samples taken from the patients and the control group. Genetic polymorphism was evaluated through the examination of reverse transcriptase polymerase chain reaction (RT PCR).GG genotype dispersion was found as 13 (40%), 7 (22%) and 4 (12%) in COM with thympanosclerosis, COM without thympanosclerosis and the control group respectively, for A/G polymorphism in inducible nitric oxide synthetase (NOS2) gene (-277). GG genotype dispersion between COM with thympanosclerosis group and the control group was statistically meaningful (p=.008).CC genotype dispersion was found as 8 (25%), 7 (22%) and 4 (12%) in the group of KOM with thympanosclerosis, COM without thympanosclerosis and the control group respectively, for superoxide dysmutase (mn-SOD) A16V (C/T) polymorphism. Even though CC genotype number increased in the group of COM with thympanosclerosis and thympanosclerosis without COM compared to the control group, no meaningful difference was found statistically.TT genotype dispersion was found as 6 (20%), 2 (6%) and 3 (9%) for COM with thympanosclerosis, COM without thympanosclerosis and the control group respectively, for A/T variation polymorphism in -21 position in catalase gene. Even though TT genotype number increased in the group of COM with thympanosclerosis compared to the control group, no statistical relevance was identified.In this study, it was identified that GG genotype of iNOS (NOS2) gene (-277) was significantly increased in patients with thympanosclerosis COM, compared to the healthy individuals. Consequently; it was concluded that genetic predisposition could play a big role in etiopathogenesis of thympanosclerosis.Keywords: Thympanosclerosis, inducible nitric oxide synthetase, superoxide dysmutase, catalase, genetic polymorphism
Genetic polymorphism of antioxidant enzymes in patient with thympanosclerosis chronical otitis media
Keywords: Kulak Burun ve Boğaz